Pengaruh Tingkat Pertumbuhan, Profitabilitas, Leverage dan Ukuran Perusahaan terhadap Kebijakan Dividen Perusahaan Makanan dan Minuman - Sherly, Sherly; Edastami, Mayangsari (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The objective of this study is to analyze the influence of certain key variables Growth rate, profitability, Leverage, and company size on dividend policy. The investigation endeavors to determine the extent to which these variables affect the aforementioned policy. Employed in this analysis are four independent variables: Growth rate, indicated by Growth; profitability, indicated by Return on Asset (ROA); Leverage, indicated by Debt to Equity Ratio (DER); and company size, indicated by FirmSize. The focus of this research is the dividend policy, represented here by the Dividend Payout Ratio (DPR) as the dependent variable. In the food and beverage sector, 96 companies were initially considered; however, only 18 of these met the requisite criteria with a total of 90 data samples eligible for analysis. Consequently, from the 480 data samples originally gathered, only 90 were suitable for further examination. It was concluded that the influence of the Growth rate on the dividend policy is both minimal and adverse. The effect of profitability on the dividend policy has similarly been identified as both slight and negative. In contrast, the research established that Leverage and company size both have a substantial and positive impact on the dividend policy. This study furnishes empirical evidence indicating that financial ratios, when contemplated by companies, facilitate the implementation of dividend policies internally.